Analisis Spasial Kerawanan Longsor Dengan Metode AHP dan SIG Kajian Mitigasi Bencana di Mojo, Kabupaten Kediri - Sari, Mita Intan; Bachri, Syamsul; Utaya, Sugeng; Suharto, Yusuf; Masruroh, Heni (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Landslides often occur in areas with steep topography and unstable geology. Mojo District, particularly the slopes of Mount Wilis, is a landslide-prone area influenced by slope steepness and land use changes. This study analyzes the main factors contributing to landslides using the Analytical Hierarchy Process (AHP) method and vulnerability mapping based on Sistem Informasi Geografis (SIG). The five main parameters used include slope steepness, soil texture, rainfall, geology, and land use. The AHP weighting results indicate slope steepness as the dominant factor (weight 0.40), followed by soil texture with a value of 0.25, rainfall 0.15, geology 0.12, and land use 0.08. The vulnerability index map is divided into three classes: low, moderate, and high. Validation using data from 13 actual landslide events shows high spatial consistency, particularly in the southwestern and central regions of Mojo District, which experience high rainfall and sandy clay soils that are less stable. The final results of this study can serve as a basis for landslide disaster mitigation efforts and spatial planning in landslide-prone areas.